UMP celebrates at Cendekia Bitara Award Night - UMP, PNC
For the third consecutive year, Universiti Malaysia Pahang (UMP) held its Cendekia Bitara Award Night to confer due recognition to its denizens who excel in the fields of research, publication, creativity and quality.